Abnormal fucosylation of alpha‐fetoprotein in patients with nonalcoholic steatohepatitis. Issue 5 (19th March 2021) - Nouso, Kazuhiro; Furubayashi, Yoshie; Kariyama, Kazuya; Wakuta, Akiko; Miyake, Nozomi; Inoue, Kanae; Nagai, Yuta; Murakami, Shiho; Adachi, Takuya; Oyama, Atsushi; Wada, Nozomu; Takeuchi, Yasuto; et al.
Abstract: Aim: Nonalcoholic steatohepatitis (NASH) is a risk factor for nonvirus‐related hepatocellular carcinoma, which is increasing in prevalence. The aim of this study was to clarify the clinical application of fucosylated alpha‐fetoprotein (AFP‐L3) in the process of nonalcoholic fatty liver (NAFL) disease development. Methods: Serum samples from 115 diabetes mellitus (DM), 36 NAFL, and 119 NASH patients were analyzed for AFP‐L3 expression using raw data of a micro total analysis system. These data were then compared with the clinical characteristics of the patients. A validation study was also undertaken with 55 samples (17 NAFL and 38 NASH). Results: Trace amounts of AFP‐L3 were detected in 3.5%, 16.7%, and 58.0% of patients with DM, NAFL, and NASH, respectively. The odds ratio of AFP‐L3 positivity for the diagnosis of NASH in multivariate analysis was 9.81 (95% confidence interval,  3.77–25.5). The rates in patients without fibrosis or with stage 1, stage 2, stage 3, and stage 4 fibrosis were 14.7%, 31.3%, 63.0%, 86.2%, and 100%, respectively. The rates were significantly increased according to the advancement of liver fibrosis ( p  < 0.001); however, no difference in the positive rate of AFP‐L3 was observed between patients with and without fatty livers and between patients with normal and abnormal transaminase. The same relationship was also observed in the validation cohort. Conclusion: Abnormal fucosylation of AFP occurred in patients with NASH, so it could be useful for the screening of NASH in patients with DM, as well as for the differential diagnosis of NASH and the evaluation of fibrosis.